CLINICAL PROFILE OF MINERAL BONE DISORDERS (RENAL OSTEODYSTROPHY) IN CHRONIC KIDNEY DISEASE PATIENTS - KHATTAR, ASHISH; RAO N, KARTHIK; PRABHU, RAVINDRA; POKHREL, BUDDHI RAJ; GURUNG, SHANTI; VARGHESE, GEORGE M; NAZEER, MOHSIN; PRIYANKA, JYOTI; TIWARI, INDU; PATIL, NAVIN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to evaluate the clinical profile of mineral bone disorders (renal osteodystrophy) in chronic kidney disease (CKD) patients. Methods: A retrospective study was performed involving 100 patients above 15 years of age with previously diagnosed chronic renal failure. A series of tests such as biochemical, radiological, and arterial calcifications were monitored. The mean age of subjects in our study was 52.54 years. Results: Biochemical tests revealed that hypocalcemia was present in 54% of the patients, and hyperphosphatemia was seen in 84% of the participants, while only 22% of the participants had high alkaline phosphate (ALP) levels. Radiological tests revealed that 39 patients had aortic calcification, 42 patients had radial artery calcification, and 27 patients had both. Subperiosteal resorption was seen on 29 participants. The majority of the vascular calcification and subperiosteal resorption was seen in patients with CKD Stage 5, and both aortic and radial artery calcifications were significantly associated with subperiosteal bone resorption. Conclusion: The results point toward a high prevalence of derangement in the mineral, vascular and valvular calcifications. Serum total ALP can serve as a biochemical marker to identify a pattern of bone turnover where intact parathyroid hormone is not available. The results highlight that serum phosphorus and Ca × P product levels were significantly associated with both aortic and radial artery calcifications. There was no significant association of these calcifications with serum calcium and ALP levels.